Antioxidation and symbiotic nitrogen fixation function of prxA gene in Mesorhizobium huakuii. Issue 10 (9th June 2019) - Wang, Sanjiao; Lu, Tiantian; Xue, Qiang; Xu, Ke; Cheng, Guojun
Abstract: Peroxiredoxins (Prxs) play an essential role in the antioxidant activity and symbiotic capacity of Mesorhizobium huakuii . A mutation in the M. huakuii prxA gene (encoding a Prx5‐like peroxiredoxin) was generated by homologous recombination. The mutation of prxA did not affect M. huakuii growth, but the strain displayed decreased antioxidative capacity under organic cumene hydroperoxide (CUOOH) conditions. The higher resistance of the prxA mutant strain compared with the wild‐type strain to more than 1 mmol/L H2 O2 was associated with a significantly higher level of glutathione reductase activity and a significantly lower level of intracellular hydrogen peroxide content. Real‐time quantitative PCR showed that under 1 mmol/L H2 O2 conditions, expression of the stress‐responsive genes katG and katE was significantly upregulated in the prxA mutant. Although the prxA mutant can form nodules, the symbiotic ability was severely impaired, which led to an abnormal nodulation phenotype coupled to a 53.25% reduction in nitrogen fixation capacity. This phenotype was linked to an absence of bacteroid differentiation and deregulation of the transcription of the symbiotic genes nifH, nifD, and fdxN . Expression of the prxA gene was induced during symbiosis. Thus, the PrxA protein is essential for antioxidant capacity and symbiotic nitrogen fixation, playing independent roles in bacterial differentiation and cellular antioxidative systems. Abstract : The Mesorhizobium huakuii prxA mutant induced partially effective nodules on Astragalus sinicus . The prxA mutant nodules had thickened cell walls in the cortex and clearly decreased the number of bacteroids. The size and structure of the bacterial strain in the mutant nodule cells indicated a general lack of bacterial differentiation into bacteroids.